Revealing Otto’s Personality Based on the Illucotionary Acts in a Man Called Otto Movie: a Study of Speech Acts - Almiah Zanjabila (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Speech acts are part of the study of pragmatics focusing on how an utterance performs an action. Speech acts can be found not only in real life but also in a literary work because a literary work is a reflection of human life and society. Movie is one of literary works that consists of speech act in it. Generally, speech acts in a movie can be found in the dialogues among characters since speech and action are the reflection of human self-expression. This research examines the use of illocutionary acts by main character in A Man Called Otto movie to reveal his personality. The purposes of this research are to find out the types of illocutionary acts produced by main character and to reveal the personality of main character. This research applies Austin’s speech acts (1962) supported by Yule’s five types of illocutionary acts (1996) and the context of situation by Brwon and Yule (1988) to describe Otto’s utterances and find out the dominant one. Furthermore, this research uses Asthon and Lee’s HEXACO model of personality to reveal main character’s personality. The type of this research is qualitative research since the data are the selected utterances of main character. The source of the data in this research is the subtitle of the movie which is accessed from the following link https://www.netflix.com/title/816162 56?s=a&trkid=13747225&trg=wha&clip=. There are 29 utterances of main character in A Man Called Otto movie indicated as illocutionary acts. The selected utterances of Otto are analyzed to find out the types of illocutionary acts used by Otto. Those types of illocutionary acts are then interpreted to know how Otto’s personality is formed by relating the use of illocutionary acts and Asthon and Lee’s HEXACO model of personality theory (2012). The result of the analysis presents that there are four types of illocutionary acts found from a total of 29 Otto’s utterances, comprising 13 utterances of directive, 10 utterances of commissive, 4 utterances of representative, and 2 utterances of expressive. Furthermore, based on the analysis of the relation between the types of illocutionary acts used by the main character in the dialogues and HEXACO model of personality, it is found that Otto’s utterances contain several traits that belong to 7 model of HEXACO personality, including 9 utterances of high-emotionality, 6 utterances of highagreeableness, 5 utterances of low-agreeableness, 4 utterances of low-emotionality, 2 utterances of low-extraversion. 2 utterances of honesty-humility and 1 utterance of highconscientiousness. It can be seen that Otto’s personality changes over time relating to the changes that happen in his life.
Reupload File Repositori 10 Februari 2026_Rudy K/Lia
Keywords: Personality Based; Illocutionary Act